Роковая ночь - Шилова Юлия Витальевна (Час криминала, 2000)
Экземпляры: ф.3 (2000) / Инвентарный номер: 42643 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Ш 59 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44